MEMBACA ULANG PEMIKIRAN GANDHI TENTANG KEMANUSIAAN - Wisarja, I Ketut; Sudarsana, I Ketut (Universitas Pendidikan Ganesha, 2018)
Mohandas Karamchand Gandhi is a humanist fighter from India. The struggles of his life both in India and in South Africa have prompted him to become a humanitarian fighter with the